The Rat Race among Fans: Tracing the Token of Love - Cheriyah, Yayah; Hadi, Amanda Rochima (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
The K-pop industry has grown even larger since merchandising came into the picture and has become an indispensable part of the industry. Across the board, fans came to a consensus about showing love and support for their idols through streaming music and purchasing merchandise. Thus, K-pop industries successfully monetize their fans through various merchandise worldwide. Despite the fact that merchandising might just be another marketing tool to alleviate the business, it has different significance for fans. By tracing fans’ roots of affection, this study tried to explore factors that predominantly drive the fans to buy and use idol goods (merchandise). Using a quantitative method with a snowballing approach as its sample, questionnaires were disseminated through various local Indonesian fandoms. The results showed that despite having limited monthly personal spending, fans still managed to collect a handful number of merchandise regardless of the cost. The study also revealed that fans were driven to use and/or buy merchandise as (1) a tool to socialize as well as self-representation within society; (2) a close representation of their idol; and (3) a way to show their affection toward their idols, which in return creating a sense of closeness toward their idol.